(untitled) (Al-Academy, 2025)
The research problem entitled (The effectiveness of the event in contemporary Iraqi painting) dealt with a study in the concept of the event. The study included four chapters. The first chapter was devoted to the theoretical framework represented by posing (the research problem), which raised the following question: What is the role of the effectiveness of the event that appeared in the arena? Iraq on the contemporary Iraqi plastic work. Did these events constitute an intellectual and aesthetic change in the contemporary Iraqi work? The first chapter included (the importance of research),(the goal of the research),and identifying (the effectiveness of embodying the event in contemporary Iraqi formation). As for the limits of the research, I focused on studying the concept of the event in the drawings of contemporary Iraqi visual artists, by analyzing some of their illustrated works from the period 2003-2020 within Iraq specifically. The chapter also included (defining terms). The second chapter is represented by the theoretical framework, which contains two sections: The first section: Introduction to the concept of event in the visual field. It dealt with the intellectual (mental) event, while the second section included: the event in contemporary formation. The third chapter(the procedural framework):I specialize in the research procedures, defining the research community and choosing the research sample from it, numbering (3) models, from the trends of conceptual art, then the research tool and sample analysis. Chapter Four: Includes the results of the sample analysis for each direction, then the results of the comparative analysis, conclusions, recommendations and proposals, a list of sources and a translation of the research summary in English.